Production of J/psi and Upsilon mesons in pp collisions at sqrt(s) = 8 TeV - collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
The production of J/psi and Upsilon mesons in pp collisions at sqrt(s) = 8 TeV is studied with the LHCb detector. The J/psi and Upsilon mesons are reconstructed in the mu+mu- decay mode and the signal yields are determined with a fit to the mu+mu- invariant mass distributions. The analysis is performed in the rapidity range 2.0